Nigella Sativa (Black Seed) as a Valuable Medicinal Plant in Uzbekistan - Shuxratullayevna, Zebo Satibaldiyeva; qizi, Tavakkalova Zuxraxon Dilmurod (American Journal of Botany and Bioengineering, 2026)
Nigella sativa, commonly known as black seed or "Qora Zira," is one of the rare and valuable medicinal plants growing in Uzbekistan. Its medicinal properties have been well-documented and utilized in various traditional medicine systems for centuries. Rich in bioactive compounds such as thymoquinone, fatty acids, and flavonoids, Nigella sativa exhibits a wide range of therapeutic effects, including antioxidant, antimicrobial, anti-inflammatory, and anti-cancer properties. This plant is increasingly recognized for its potential in modern medicine and agricultural applications, particularly in regions like Uzbekistan, where its cultivation can offer economic and health benefits. This review explores the medicinal significance, bioactive components, and applications of Nigella sativa, with a particular focus on its role within Uzbekistan’s ecological and agricultural context.